Evaluasi Saluran Drainase Di Jalan Purnama Kelurahan Parit Tokaya Kecamatan Pontianak Selatan - Perangin Angin, Imanuel Kemenangenta; Moambura, Ayub Konstantinus; nernawani, Nernawani (Politeknik Negeri FakFak, 2024)
Pontianak has a low topographic condition with the state of the water cathment area that has changed function into a residential area. Pontianak city also has a high rainfall intensity every year. Due to the high intensity of rainfall, some of the rainwater that falls on the earth’s surface is absorebed into the soil which is called infiltration and some flows into surface runoff. To control the surface runoff, a good drainage system must be created. Good drainage channels can help control surface runoff due to high rainfall intensity. In this study, the drainage channel studied was the drainage channel on Purnama 1 street, Parit Tokaya Village, South Pontianak District, Pontianak City, Which currently has a width and height of 7 meters and 1,5 meters. Where from the evaluation of the existing drainage is not optimal optimal in overcoming surface runoff caused by high rainfall in the area. From the results of the calculation analysis the optimal drainage channel in the area has dimensions of 7 meters wide and a depth 1,6714 meters, and a guard height of 0,9141 meters with a surface flow runoff discharge that can be accommodated from the annual daily rainfall data for a 10 years period of 17,5499 .